The Effect Of Baby Massage Toward Baby Sleep Pattern: A Quasy Experiment Study - Pebrianthy, Lola; Aswan, Yulinda; Sari Batubara, Novita; Nasution, Ayannur; Siregar, Sriyanti; Wari Harahap, Yanna (KnE Social Sciences, 2023)
Sleep provides a positive effect for the development of the baby because it can stimulate the growth of the baby’s brain. This study aims to identify the effect of baby massage toward baby sleep patterns. The researchquasy experiments with a sample number of 33 babies. The sampling technique used total sampling with data analysis t-dependent test and Mc Nemar test.The resultsin the sleeping position of babies before and after the massage where the time needed for the baby to fall asleep = 18.33 minutes (p value = 0.001), the total sleep for babies in 24 hours = 13.36 hours (p value = 0.008), the number of hours of sleep for infants at night = 9.78 hours (p value = 0.015), the frequency of babies waking at night = 3 times (p value = 0.008), and the majority of babies waking up did not cry (p value = 0.000). The results of this study prove that baby massage has an effect on baby’s sleep patterns. Therefore it is important for midwifery officers to inform and teach baby massage techniques to the baby’s parents so that it helps in overcoming the baby’s sleep problems. Keywords: Baby massage; baby’s brain; baby sleep pattern